PENERAPAN STRATEGI PEMBELAJARAN PENINGKATAN KEMAMPUAN BERPIKIR (SPPKB) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IVB SD NEGERI 183 PEKANBARU - Isma Safitri Harahap; Mahmud Alpusari; Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem in this research is the low of Science learning outcomes. This is seen from the average student test scores were 64.45, where minimum completeness criteria applied 75. Because of these problems, an action research need to be conducted by applying Learning Strategies Enhancing Thinking Skills. The purpose of this research is to enhance the students' Science Learning Outcomes in 4B Grade students of SD Negeri 183 Pekanbaru at Academic Year 2015/2016 with the number of 37 students. The research was conducted in two cycles, implemented in the second semester, the instrument consists of learning tools and data collection instruments. The data in this research is the observation sheet teacher activity, the student activity observation sheet, and the daily tests. Based on the analysis of the observation sheet activities of teachers and students saw an improvement that activity of teacher in the first cycle reaches 75.00%, second cycle reaches 91,66%, while in the student activity reached 70.83% for the first cycle and the second cycle reaches 91.66%. Analysis of the data showed improvement student learning outcomes that in the first cycle the average is 73.24 with 62.16% classical completeness, while in the second cycle the average is 87.29 with 86.48% classical completeness. This shows that the application of Learning Strategies Enhancing Thinking Skills can improve Science Learning Outcomes of IVB Grade Students SD Negeri 183 Pekanbaru.KeyWord: Learning Strategies Enhancing Thinking Skills, Science Learning Outcomes